Exploring the state of health and safety management system performance measurement in mining organizations. (March 2016) - Haas, Emily Joy; Yorio, Patrick
Graphical abstract: Example of specific health and safety management performance indicators being (1) applied within three categories and (2) implemented using multiple methods and measures to engage in safety climate activities across the Plant-Do-Check-Act cycle. Highlights: We collected data from 9 mine H&S professionals about HSMS performance measurement. Qualitative content analysis was used to classify over 1200 performance metrics. The analysis revealed interventions, organizational and worker performance categories. Qualitative/quantitative methods should be incorporated into performance measures. Objective /subjective indicators should be incorporated into performance measures. Abstract: Complex arguments continue to be articulated regarding the theoretical foundation of health and safety management system (HSMS) performance measurement. The culmination of these efforts has begun to enhance a collective understanding. Despite this enhanced theoretical understanding, however, there are still continuing debates and little consensus. The goal of the current research effort was to empirically explore common methods to HSMS performance measurement in mining organizations. The purpose was to determine if value and insight could be added into the ongoing approaches of the best ways to engage in health and safety performance measurement. Nine site-level health and safety management professionals were provided with 133 practices corresponding to 20 HSMS elements, each fitting into the plan, do, check, act phases common to most HSMS. Participants were asked to supply detailed information as to how they (1) assess the performance of each practice in their organization, or (2) would assess each practice if it were an identified strategic imperative. Qualitative content analysis indicated that the approximately 1200 responses provided could be described and categorized into interventions, organizational performance, and worker performance . A discussion of how these categories relate to existing indicator frameworks is provided. The analysis also revealed divergence in two important measurement issues; (1) quantitative vs qualitative measurement and reporting; and (2) the primary use of objective or subjective metrics. In lieu of these findings we ultimately recommend a balanced measurement and reporting approach within the three metric categories and conclude with suggestions for future research.